Determination of Atmospheric Parameters of B-, A-, F- and G-Type Stars Lectures from the School of Spectroscopic Data Analyses - Niemczura, Ewa.; Smalley, Barry; Pych, Wojtek; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book introduces the theory of stellar atmospheres. Almost everything we know about stars is by analysis of the radiation coming from their atmospheres. Several aspects of astrophysics require accurate atmospheric parameters and abundances. Spectroscopy is one of the most powerful tools at an astronomer s disposal, allowing the determination of the fundamental parameters of stars: surface temperature, gravity, chemical composition, magnetic field, rotation and turbulence. These can be supplemented by distance measurements or pulsation parameters providing information about stellar interior and stellar evolution, otherwise unavailable. The volume is based on lectures presented at the Wrocław's Spectroscopic School aimed at training young researchers in performing quantitative spectral analysis of low-, mid-, and high-resolution spectra of B, A, and F-type stars.
Keywords: Earth sciences; Planetology; Observations, Astronomical; Astronomy -- Observations; Space sciences; Earth Sciences; Planetology; Astronomy, Observations and Techniques; Extraterrestrial Physics, Space Sciences; Electronic books